(untitled) (Journal of Applied Oral Science, 2022)
Objectives: The purpose of this study was to determine the impact of nonsurgical periodontal therapy considering the salivary stress-related hormone and cytokine levels in the gingival crevicular fluid (GCF) on pregnant and nonpregnant women. Material and Methods: Thirty non-pregnant (control group) and 30 pregnant women (test group) that met the study inclusion criteria were chosen. Only participants with gingivitis were included. Clinical data and samples of GCF and saliva were collected at baseline and after periodontal therapy. The levels of interleukin-1 beta (Κ-1β) and IL-10, and concentration of salivary chromogranin A (CgA) hormone were analyzed by enzyme-linked immunosorbent assay (ELISA). The repeated measures analysis of variance was used for intragroup and intergroup analyses. Results: A major decrease in the gingival inflammation was observed in both groups after periodontal therapy (p<0.05). Periodontal treatment decreased the level of IL-1β in GCF (p<0.05) in control group, but no statistical difference was determined for GCF IL-1β in the test group. However, after periodontal therapy, the CgA hormone concentration was reduced in both groups (p<0.05). However, there was no difference in salivary CgA concentration, GCF IL-10 levels, and perceived stress scale (PSS)-10 between the groups (p>0.05). Conclusions: Within the limitations of this study, periodontal therapy significantly improved the periodontal status and stress level. In addition, the severity of the gingival inflammation during pregnancy was related to stress. However, further studies will be needed to substantiate these early findings